2018
DOI: 10.1002/cncr.31870
|View full text |Cite
|
Sign up to set email alerts
|

Survival, local control, and health‐related quality of life in patients with oligometastatic and polymetastatic spinal tumors: A multicenter, international study

Abstract: the AO Spine Knowledge Forum Tumor 17

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 30 publications
1
28
0
1
Order By: Relevance
“…Specific to spine oligometastases, Barzilai et al reported results from the AO Spine multicenter prospective cohort Epidemiology, Process, and Outcomes of Spine Oncology (EPOSO) study (30). Patients with oligometastatic disease (defined as <5 metastases) showed evidence of better survival compared to those with polymetastatic disease (>5 metastases).…”
Section: Spine Metastases and Sbrtmentioning
confidence: 99%
“…Specific to spine oligometastases, Barzilai et al reported results from the AO Spine multicenter prospective cohort Epidemiology, Process, and Outcomes of Spine Oncology (EPOSO) study (30). Patients with oligometastatic disease (defined as <5 metastases) showed evidence of better survival compared to those with polymetastatic disease (>5 metastases).…”
Section: Spine Metastases and Sbrtmentioning
confidence: 99%
“…He compared the 1-year Local Control rate of each of the treatments. It was found that surgery with or without RT (n=129) had 65.5% 1-year local control, cEBRT (n=23) had 57.1% 1-year local control rate and SRS (n=63) had 84.8% 1 year local control rate [9]. The Kaplan Meier Curves further supporting this evidence can be found in Appendix A.…”
Section: Introductionmentioning
confidence: 60%
“…Some studies included comparison with polymetastatic disease of spine and compared outcomes, this was excluded when analyzing Kaplan Meier Curves or data tables. Only statistically significant data was chosen to make valid comparisons between Local Control or Overall Survival rates [7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 The oligometastatic state is commonly defined as 5 or fewer metastatic sites systemically. 3 In the spine, bony metastases can cause complications such as severe pain, neurological compromise, and mechanical instability leading to vertebral compression fracture (VCF). 4 Hence, one of the primary goals of care for spine metastases is longterm tumour control with ablative therapy.…”
Section: Introductionmentioning
confidence: 99%